2021
DOI: 10.1080/08098131.2021.1934088
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of emotion-regulating improvisational music therapy for young adult students with depressive symptoms: A process evaluation

Abstract: Introduction: Depression can be a serious problem in young adult students. There is a need to implement and monitor prevention interventions for these students. Emotion-regulating improvisational music therapy (EIMT) was developed to prevent depression. The purpose of this study was to evaluate the feasibility of EIMT for use in practice for young adult students with depressive symptoms in a university context. Method: A process evaluation was conducted embedded in a larger research project. Eleven students, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…Although these data are preliminary, it may suggest that adding music to standard psychological treatments can play a role in the treatment of young people with ADHD since it provides them with a self-regulatory system (Antonietti et al, 2018). Many music therapists consider emotion regulation to be a potential benefit of music-based skills training and use music in therapeutic relationships to improve adolescents’ ability to manage/regulate their own emotions and use adaptive cognitive-emotional strategies (Aalbers et al, 2021; Marik & Stegemann, 2016). Since emotion regulation considered as an essential component of broader self-regulation system (Diamond & Aspinwall, 2003; Geva & Feldman, 2008), promotion of self-regulation competence through music helps them in the top-down and effortful executive control and enables them to manage/regulate the emotions and impulsive tendencies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although these data are preliminary, it may suggest that adding music to standard psychological treatments can play a role in the treatment of young people with ADHD since it provides them with a self-regulatory system (Antonietti et al, 2018). Many music therapists consider emotion regulation to be a potential benefit of music-based skills training and use music in therapeutic relationships to improve adolescents’ ability to manage/regulate their own emotions and use adaptive cognitive-emotional strategies (Aalbers et al, 2021; Marik & Stegemann, 2016). Since emotion regulation considered as an essential component of broader self-regulation system (Diamond & Aspinwall, 2003; Geva & Feldman, 2008), promotion of self-regulation competence through music helps them in the top-down and effortful executive control and enables them to manage/regulate the emotions and impulsive tendencies.…”
Section: Discussionmentioning
confidence: 99%
“…The intervention protocol consisted of 12 individual weekly sessions each lasting 60 min and followed standard-practice CBT for adolescents with ADHD (Sprich & Burbridge, 2019; Sprich et al, 2015; Sprich & Safren, 2020) and adjunctive music-based treatment to enhance emotion-regulation skills. The conceptual framework, strategies, and targets for the latter were adapted from theory and research related to both music-based interventions (Aalbers et al, 2019, 2021), and emotion-regulation skills (Marik & Stegemann, 2016; Rosen et al, 2019). We chose music-based emotion-regulation strategies to augment standard-practice CBT for ADHD on the basis of its track record in addressing emotion-regulation deficits (Dursun et al, 2021; Zhang et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This questionnaire was filled in after each group session and each individual session. Treatment integrity was considered sufficient when both therapist adherence and competence reached a percentage of >60% at group level [ 34 ].…”
Section: Methodsmentioning
confidence: 99%
“…Despite music therapists working with diverse age groups and diagnoses, only three studies have been published to date on the effects of music therapy with university or college students (26)(27)(28). Each of these studies reported on the benefits of engaging in music therapy to treat a clinical symptom or developmental difficulty; however, only one of the studies implemented a randomized controlled trial (RCT) design (27) and none included a physiological measure.…”
Section: Introductionmentioning
confidence: 99%